2020
DOI: 10.2196/17065
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Chatbot for Depression: Descriptive Study of Usage

Abstract: Background Chatbots could be a scalable solution that provides an interactive means of engaging users in behavioral health interventions driven by artificial intelligence. Although some chatbots have shown promising early efficacy results, there is limited information about how people use these chatbots. Understanding the usage patterns of chatbots for depression represents a crucial step toward improving chatbot design and providing information about the strengths and limitations of the chatbots. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 24 publications
0
39
1
Order By: Relevance
“…Users can engage with Tess interventions through text message conversations or Facebook Messenger. Other studies provide more information on how Tess works ( 9 ). Recruitment advertisements were delivered via Facebook stating that the chatbot intended to reduce social isolation, loneliness, and depression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Users can engage with Tess interventions through text message conversations or Facebook Messenger. Other studies provide more information on how Tess works ( 9 ). Recruitment advertisements were delivered via Facebook stating that the chatbot intended to reduce social isolation, loneliness, and depression.…”
Section: Methodsmentioning
confidence: 99%
“…There are several mental health and well-being chatbots that have been developed and are used commercially including Kokobot ( 7 ), Replika ( 6 ), Shim ( 8 ), Tess ( 9 , 10 ), Woebot ( 11 ), and Wysa ( 12 ). These chatbots have been shown to lead to improvements in mood and symptoms of mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Users can chat with Tess through text message conversations or Facebook Messenger. Other studies provide more information on how Tess works ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, there has been an increased interest in the integration of chatbots for assessment (20) and treatment of depression (21)(22)(23). While Fitzpatrick et al (22) and Fulmer et al (23) reported improvements in depressive symptoms using an interactive version of the PHQ-9 through a chatbot, the psychometrics properties have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chatbots for mental health can be conceptualized as interactive self-help. Researchers at i4Health have studied how users engaged with a Chatbot's (Tess) conversations designed for management of depressive symptoms, finding that most U.S. adults users completed a mean of 2.18 conversations with Tess (Dosovitsky et al, 2020). While this number may seem low, it is higher than the mean number of modules completed in studies of most smartphone apps.…”
Section: On Texting and Chatbots For Depressionmentioning
confidence: 99%